The demand for food grain in China: new insights into a controversy - Zhang, Xiaobo; Mount, Timothy D.; Boisvert, Richard N. (Cambridge University Press, 2001)
There is a substantial controversy in the economics literature over the magnitude of the expenditure elasticity for food grain in China that is caused, to a large extent, by whether time-series or cross-section data are used in the analysis. A set of reasonable elasticities for a complete demand system is estimated by using a panel of county level data in Guangdong Province for the last ten years. The results show that food grain has a small positive income elasticity, implying that food grain is not an inferior good in China. The reason that consumption per capita has not increased during a period of rapid economic growth in income is that the relative prices of the food and non-food substitutes for food grain have decreased.